2007
DOI: 10.1093/ecam/nem030
|View full text |Cite
|
Sign up to set email alerts
|

Chondroprotective Potential of Fruit Extracts of Phyllanthus emblica in Osteoarthritis

Abstract: There is a need for effective nutraceuticals for osteoarthritis care. The fruit of Phyllanthus emblica is used as a powerful rejuvenator in Ayurvedic medicine. This study measured the chondroprotective potential of P. emblica (‘Amalaki’) fruits in vitro. We used aqueous extracts of unprocessed P. emblica fruit powder (powder A), and the powder obtained after hot water extraction and drying of powder A (powder B). Chondroprotection was measured in three different assay systems. First, we tested the effects of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
(20 reference statements)
1
27
0
Order By: Relevance
“…From these pre-clinical results, the authors concluded that TG could be used as a chondroprotective agent in the management of arthritis. Recently, Sumantran et al [191] demonstrated the chondroprotective role of aqueous extracts of unprocessed and processed (hot water extraction of dry fruit powder) dry fruit powder of Phyllanthus emblica. Both the extracts inhibited HAase and collagenase type 2, the ECM degrading enzymes.…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…From these pre-clinical results, the authors concluded that TG could be used as a chondroprotective agent in the management of arthritis. Recently, Sumantran et al [191] demonstrated the chondroprotective role of aqueous extracts of unprocessed and processed (hot water extraction of dry fruit powder) dry fruit powder of Phyllanthus emblica. Both the extracts inhibited HAase and collagenase type 2, the ECM degrading enzymes.…”
Section: Medicinal Plantsmentioning
confidence: 99%
“…Moreover, it has also been reported to possess antioxidant Reddy et al, 2009), antiaging (Datta et al, 2009), chondroprotective (Sumantran et al, 2008), chemoprotective (Sultana et al, 2008), anti-inflammatory (Sharma et al, 2003;Nicolis et al, 2008), hepatoprotective (Panchabhai et al, 2008), antibacterial (Saeed and Tariq, 2007), antipyretic and analgesic (Perianayagam et al, 2004) activities. Despite the availability of various studies on different aspects of Phyllanthus emblica and a preliminary report showing its efficacy in diarrhea (Perianayagam et al, 2005), it has not been widely studied for the possible mode(s) of action using both the in vivo and in vitro assays, for its medicinal use in hyperactive gut disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous extracts of amalaki powder have also been found to inhibit hyaluronidase and collagenase in vitro . In addition, amalaki extract exhibited signifi cant longterm chondroprotective activity in cartilage explants from 50% of the patients tested who suffered from osteoarthritis [26] .…”
Section: Efficacy Of Ayurvedic Medicinementioning
confidence: 95%